Evidencias de validez para la escala informatizada de actitudes hacia la estadística ESATS - Medeiros Vendramini, Claudette Maria (2014)
This study aimed to verify the validity evidences of the electronic scale of attitudes towards statistics eSATSportuguês through Rasch model. A sample of 137 Brazilian students, selected for convenience, participated in this study. They were aged 20-55 (M=28.71; DP=7.77), 79.6% female, enrolled in the last semester from graduation courses of a private university in São Paulo state, and had already attended a Statistics subject. The participants answered the 28-item, 7-point Likert-type scale, in computer laboratories. The results indicated a good fit of the items to Rasch model, and the scale’s good psychometric properties, making it a good instrument to measure the construct attitude. The sample’s average attitude towards statistics was more positive rather than negative.